Implementation of Daily Religious Guidance as a Pedagogical Strategy in Elementary Schools - Suryono, Suryono; Arqam, Mhd. Lailan; Yoyo, Yoyo (Journal of Indonesian Progressive Education, 2025)
This research aims to analyze the implementation of daily religious guidance as a pedagogical strategy in elementary schools. This study is motivated by the urgency of strengthening character education thru a structured and sustainable habituation approach within the school environment. This research uses a qualitative approach with a case study design. The research subjects include the principal, Islamic Religious Education teachers, classroom teachers, students, and parents. Data were collected thru interviews, observations, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and conclusion drawing.The research results show that the religious guidance program at Sogan Public Elementary School is implemented systematically thru structured and integrated daily activities, such as Duha prayers, memorization of short surahs, congregational prayers, daily prayers, and social habits like charity and respectful behavior. Supervision is carried out collaboratively by the principal and teachers.Research findings affirm that daily religious guidance is not merely a routine activity, but rather serves as an effective experiential-based pedagogical strategy in internalizing religious values and shaping students' character thru continuous habituation.